Solidariteit en slachtofferschap De morele betekenis van criminaliteit in een postmoderne cultuur - Boutellier, Hans (Amsterdam Academic Archive, 2008)
What is it that really binds Dutch people together? That's the central question of many public debates.This study focuses on the the role of victimhood on our concept of society. Drawing on the works of the American philosopher Richard Rorty, the author discusses morality, criminality, religion, sexual abuse and legalisation of prostituiton.